Im Blick zurück entstehen die Dinge - Maxim Görke (Recherches Germaniques)
Ever since the journal was founded, the transfer of the German-French culture has played an important role in Recherches germaniques. Four major subjects can be identified: the German reception of French thinkers, the French reception of German-language intellectuals, comparative studies and the German perception of French statesmen. In addition, there are some studies on trilingual Alsatian protagonists. Taken together, all the studies presented in thisarticle show the sustainability and longevity of this bi-national exchange.